PERANCANGAN VIDEO CELURIT SEBAGAI UPAYA MENGINFORMASIKAN SALAH SATU SIMBOL BUDAYA MASYARAKAT MADURA - Oktaviyan, Erwin; Yurisma, Dhika Yuan; Prasetya, Ardian Jaya (Jurnal Art Nouveau, 2018)
the problem in this study is how to introduce celurit from the side that is rarely known by the public where celurit has historical values and functions and types of different types. celurit is known in the community as a sharp weapon that is used more toward the negative like the action that leads to criminal acts it results in positive values that exist in the celurit began to fade so that the more popular kerurit as a sharp weapon used for criminal acts rather than positive value. introducing celurit with video media is urgently needed to provide new information about the celurit rarely known by the general public